PENGARUH KEPEMIMPINAN FASILITAS KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PERANGKAT DESA DI KECAMATAN LUBUK BATANG KABUPATEN OGAN KOMERING ULU - Novarianti, Onih (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This research aims to analyze the influence of leadership, work facilities, and work motivation on the performance of village officials in Lubuk Batang District, Ogan Komering Ulu Regency. This study employs a quantitative approach. Data was collected through survey methods by distributing a questionnaire instrument to 64 village officials in Lubuk Batang District, Ogan Komering Ulu Regency, as the research population. The analysis method used is tabulation to answer the research objectives, utilizing a Likert scale table and regression analysis. The variables in this research are as follows: the independent variables are Leadership, Work Facilities, and Work Motivation, while the dependent variable is the performance of village officials. The results of the analysis indicate that Leadership has a positive and significant effect on the performance of village officials, Work Facilities also have a positive and significant effect on the performance of village officials, and Work Motivation likewise has a positive and significant effect on the performance of village officials. Thus, it is recommended that agencies pay more attention to leadership, work facilities, and work motivation as they can directly or indirectly influence performance.